Application of topology optimization technique to size the NGCTR-TD engine mount at high temperature using unconventional materials - Nigrelli, L.; Sala, G.; Patricelli, L. (My University, 2021)
Within the CS2 FRC framework Leonardo Helicopters is leading the team who is going to develop new technologies and solutions for future tiltrotors. The engine mounts turned out to be a design challenge since they have a great impact on the overall weight of the Technological Demonstrator under development and they need to be complaint with very stringent mechanical requirements in a very bad thermal environment (temperatures up to 1100 °C as per certification requirements). The Topology Optimization technique, using Optistruct, was used to investigate a new design of the engine mount of the NGCTR-TD at high temperature. The design guessed was optimized at three different temperatures in the range RT-1000 °C, comparing the use of Stainless steel and Titanium alloy, with the same problem 18 set up to compare the benefits, in terms of mass reduction, of each material. The results demonstrated that, at temperatures under 538 °C, the introduction of the Titanium alloy guarantees a remarkable mass saving for the current design, but at temperatures above 1000 °C, the benefits obtain-able were nullified by the overcoming of the stress constraints, also in areas not subjected to Topology Optimization. In parallel to this work, the possible benefits of introducing a fire tested thermal coating in the design were investigated through thermal analysis with Acusolve, in order to find the most suitable arrangement of layers to protect the structure. The proposed solution proved to protect the engine mount from high temperatures, reaching on the inside a temperature below 250 °C, thus allowing to investigate the use of Aluminum alloy which is an unconventional choice for this type of application. After being Topology Optimized and despite of the contribution introduced by the thermal coating, this solution demonstrated to produce the greatest mass saving compared with the other materials, electing the Aluminum alloy to be used for the next stages of the design of the engine mount.